Analisis Yuridis terhadap Pelanggaran Syarat Objektif dalam Pasal 1320 Kitab Undang-Undang Hukum Perdata - Dela Meilany; Fariz Azka Abdullah; Ivan Rigi Azasa; Mozza Ayudhia (Letterlijk, 2024)
This research aims to analyze and seek information regarding violations of the objective requirements in Article 1320 of the Civil Code. Buying and selling is a type of agreement regulated in the Civil Code, namely that one party binds himself to hand over an object and the other party to pay the price that has been promised or determined. The research method used in this research uses a normative method, namely the rules of literature study, namely in the form of collecting and conducting a study of several library sources. This research discusses the legal regulations governing the buying and selling of illegal Mystery City goods (Mistery Box) in Indonesia, as well as the implications of the practice of buying and selling illegal Mistery Box goods on the enforceability of agreements and consumer protection. Buying and selling Mystery Boxes via the internet has a different appeal from regular online buying and selling. Buyers do not need to spend a lot of time choosing which product they want because they only need to spend money and pay for the contents of the box in the mystery box that is already visible in the market. The legal consequences that often arise in Mystery Box buying and selling transactions in online shops are unlawful acts and breaches of contract. In cases of default, the buyer may be subject to legal sanctions, including payment of damages to the seller and payment of court costs if the problem is resolved through court.